2009
DOI: 10.1007/s11916-009-0073-2
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms by which sleep disturbance contributes to osteoarthritis pain: A conceptual model

Abstract: Sleep disturbance is prevalent in aging and painful rheumatologic populations, but it has largely been a neglected dimension of the routine clinical care of arthritis patients. Pain associated with osteoarthritis (OA) is a leading cause of disability worldwide, and factors that contribute to pain in OA are poorly understood. Sleep disturbance is not only a consequence of pain, it is also likely to play an integral role in pain expression. Emerging research suggests that many patients with OA demonstrate signs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
99
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(115 citation statements)
references
References 72 publications
10
99
0
1
Order By: Relevance
“…In addition, increase sleep fragmentation and shorter sleep duration may promote hyperalgesia through increased inflammatory activity. 29 Nevertheless, the small effects observed in the present study should be considered with the qualification that they represent self-report responses observed from day-to-day; these small daily effects, however, may accumulate over years of coping with SCD and thus integratively represent a contributor to disease burden and poor quality of life in these patients. Future research and treatment studies should consider the interacting effects of sleep fragmentation and sleep duration and seek to determine if specifically altering sleep continuity in patients with SCD yields clinically meaningful changes in SCD pain.…”
Section: Discussionmentioning
confidence: 79%
“…In addition, increase sleep fragmentation and shorter sleep duration may promote hyperalgesia through increased inflammatory activity. 29 Nevertheless, the small effects observed in the present study should be considered with the qualification that they represent self-report responses observed from day-to-day; these small daily effects, however, may accumulate over years of coping with SCD and thus integratively represent a contributor to disease burden and poor quality of life in these patients. Future research and treatment studies should consider the interacting effects of sleep fragmentation and sleep duration and seek to determine if specifically altering sleep continuity in patients with SCD yields clinically meaningful changes in SCD pain.…”
Section: Discussionmentioning
confidence: 79%
“…Interestingly, the multivariate analysis revealed that severity of sleep problems remained significant in the multivariate model of predictors of pain severity. It is plausible that physical pain disrupts sleep quality; however, sleep problems may also exacerbate pain (Morphy et al, 2007;Smith et al, 2009). In accordance with other research studies pointing toward a significant influence of pain on attention (Moore et al, 2009), we observed a significant bivariate association between pain and impulsivity.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the physiological interaction between sleep and pain in general-and in mild TBI in particularremains unclear, it is possible that central thalamic processes play a role in both complaints, with diffuse nociceptive inhibitory control and inflammation suggested as potential mechanisms. 45 The literature strongly associates pain with sleep problems in mTBI, based on questionnaires and reports. 22,25 Pain as well as post-traumatic stress disorder were also shown to be significantly associated with sleep problems, known as the ''polytrauma clinical triad.''…”
Section: Discussionmentioning
confidence: 99%